Vertebral artery hypoplasia and hemodynamic impairment in transient global amnesia: a case control study - Werner, Ralph; Ekstrom, Alexandra; Kureck, Ingo; Wöhrle, Johannes C. (Frontiers in Neurology, 2024)
The aetiology of transient global amnesia (TGA) is still a matter of debate.Besides ischemia of the mesial temporal lobe including the hippocampus, migraine-like mechanisms, epileptic seizures affecting mnestic structures, or venous congestion in the (para)hippocampal area due to jugular vein insufficiency have been discussed.We assessed the diameters of the intracranial arteries of TGA patients compared to controls to identify differences that support the hypothesis of reduced hippocampal perfusion as a pivotal factor in the pathophysiology of TGA. For that purpose, we reviewed magnetic resonance imaging time of flight angiographies (TOF-MRA) that were acquired during inpatient treatment of 206 patients with acute TGA. The diameters of the vertebral artery (VA) in the V4 segment, the proximal basilar artery, and the internal carotid arteries were measured manually. We compared the findings with TOF-MRA images of an age and sex matched control group of neurological patients without known cerebrovascular pathology.In TGA patients the diameter of the right VA was significantly (p<0.01) smaller compared to controls (2.09 mm vs. 2.35 mm). There were no significant differences in the diameters of the other vessels. Only the fetal variant of the posterior cerebral artery was slightly more common in TGA.The smaller diameter (hypoplasia) of the right VA supports the hypothesis of a contribution of hemodynamic factors to the pathophysiology of TGA. The fact that hypoplasia represents a congenital condition might be the explanation why previous studies failed to find an increased rate of the classical (acquired) vascular risk factors.